Familia disfuncional y el impacto psicosocial en un adolescente - Chavez Garcia, Miryan Maroly (2020)
The present study has as its theme: dysfunctional family and the psychosocial impact on a teenager and as an objective, to identify how a dysfunctional family influences and what psychosocial impact it has on a 14 year old teenager, according to the relationship of the variables the diagnostic criteria were determined , the psychosocial impact and the psychotherapeutic intervention will be used, in which techniques and instruments will be used such as: clinical history, clinical observation, psychometric techniques such as the family functioning perception test (FF-SIL) and the SCL-90-R inventory . The adolescent presents criteria for the diagnosis of adjustment disorder (F43.2), there being a relationship between family dysfunctionality in which she lives and her psychosocial well-being, being affected in her mood, interpersonal relationships, hopelessness, stress due to family factors and Therefore, psychotherapeutic intervention was performed under the systemic therapy model.